2011
DOI: 10.1136/gutjnl-2011-300936
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium infantis35624 administration induces Foxp3 T regulatory cells in human peripheral blood: potential role for myeloid and plasmacytoid dendritic cells

Abstract: BackgroundIntestinal homoeostasis is dependent on immunological tolerance to the microbiota. Objective To (1) determine if a probiotic could induce Foxp3 T cells in humans; (2) to elucidate the molecular mechanisms, which are involved in the induction of Foxp3 T cells by human dendritic cells. Design Cytokine secretion and Foxp3 expression were assessed in human volunteers following Bifidobacterium infantis feeding. Monocyte-derived dendritic cells (MDDCs), myeloid dendritic cells (mDCs) and plasmacytoid dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
185
2
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(200 citation statements)
references
References 42 publications
6
185
2
7
Order By: Relevance
“…An increasingly recognised feature of immunoregulatory microbes is their ability to induce Treg cells [87]. It has been demonstrated that oral consumption of Bifidobacterium infantis 35624 is associated with enhanced IL-10 secretion and FoxP3 expression in human peripheral blood [89]. Murine studies have demonstrated that B. infantis administration results in an increase in CD4 + CD25 + FoxP3 + lymphocytes [90].…”
Section: Use Of Probiotics For the Induction Of Regulatory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasingly recognised feature of immunoregulatory microbes is their ability to induce Treg cells [87]. It has been demonstrated that oral consumption of Bifidobacterium infantis 35624 is associated with enhanced IL-10 secretion and FoxP3 expression in human peripheral blood [89]. Murine studies have demonstrated that B. infantis administration results in an increase in CD4 + CD25 + FoxP3 + lymphocytes [90].…”
Section: Use Of Probiotics For the Induction Of Regulatory T Cellsmentioning
confidence: 99%
“…Murine studies have demonstrated that B. infantis administration results in an increase in CD4 + CD25 + FoxP3 + lymphocytes [90]. Moreover, it has been seen that, in vitro human dendritic cells stimulated with B. infantis selectively promoted the upregulation of FoxP3 expression in naïve lymphocytes [89]. Furthermore, B. infantis has been demonstrated to reduce symptom severity in patients with inflammatory bowel syndrome in two placebo-controlled human clinical studies [91,92].…”
Section: Use Of Probiotics For the Induction Of Regulatory T Cellsmentioning
confidence: 99%
“…15 Through the engagement of innate receptors, such as Toll-like receptors (TLRs), nucleotide-binding oligomerization domains (NODs) or C-type lectin receptors, probiotic lactobacilli and bifidobacteria induce distinct innate responses and cytokine profiles that subsequently shape T-helper cell responses. [16][17][18] There is accumulating evidence that certain strains possess intrinsic Th1-type immunomodulatory properties, 18,19 while others are able to induce regulatory responses. 17,20,21 Transforming growth factor (TGF)-b is present at high concentrations in the intestine and has a crucial involvement in modulating the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] There is accumulating evidence that certain strains possess intrinsic Th1-type immunomodulatory properties, 18,19 while others are able to induce regulatory responses. 17,20,21 Transforming growth factor (TGF)-b is present at high concentrations in the intestine and has a crucial involvement in modulating the immune response. 22 It has been shown to inhibit the proliferation and differentiation of both B and T cells, 23 and altered TGF-b signaling has been linked to the development of allergic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Konieczna et al (2011) determined that a probiotic could induce Foxp3 T cells in humans. Volunteers fed with B. infantis displayed selective increase in secretion of interleukins and enhanced Foxp3 expression in peripheral blood.…”
Section: Milk Allergymentioning
confidence: 99%